Pengaruh Pengelolaan Tata Usaha Terhadap Pelayanan Administrasi Sekolah Pada UPTD SMA Negeri 3 Merauke. - Hardiman, Tri; Reginalis, Maria; Rada, Felix; Uruilal, Jolanda (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2026)
This study examines the relationship between administrative management and school administrative services at the Technical Implementation Unit of Merauke State Senior High School 3, as well as the extent to which administrative management influences these services. The research employed a total sampling method with a sample size of 35 participants. The proposed hypothesis was H0: There is no relationship between administrative management and school administrative services at the Technical Implementation Unit of Merauke State Senior High School 3.n Unit of the Merauke State Senior High School 3, while Ha = There is a relationship between Administrative Management and School Administrative Services at the Technical Implementation Unit of the Merauke State Senior High School 3. To find the correlation between the two variables, the product moment correlation formula was used, and to determine the magnitude of the relationship, the coefficient of determination formula was used. The results of the study proved that there was an influence between variables X and Y. The correlation test results showed a very strong correlation of 0.81. while the determination test showed that the coefficient of determination value was 65.61%, with the remaining 34.39% indicating that there were other influencing factors.